(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The most frequent cancer in India is oral cancer, which has been epidemiologically associated to chewing betel nut and other carcinogens. But the p53 and p15 genes showed a number of point mutations. In order to determine hereditary risks as well as indicators for oral cancer and wound healing, this review was undertaken. In terms of genotype frequencies and cigarette smoking dose, polymorphisms of the CYP1A1 and GSTM1 genes are linked to malignancies caused by tobacco use. Additionally, E6/E7 expression was discovered in malignancies, the majority of which originated in the oropharynx. p53 is approximately seven times more sensitive to E6-mediated proteolytic degradation when homozygous arginine is present at codon 72. As one of the main mitogens involved in cutaneous wound healing, erythropoietin, vascular permeability factor (VPF, commonly known as vascular endothelial growth factor or VEGF), and PDGF have all been identified. Cell survival is improved when NF-kB is activated. In tonsilar cancer, the presence of the human papilloma virus is a markedly positive prognostic feature that can be employed as a marker to optimise patient care.